Pupils’ Adaptability at School, a Balance Between Demands and Resources? - Oger, Marie; Broc, Guillaume; Martin-Krumm, Charles; Le Roux, Fleur; Muller, Anita; Tarquinio, Cyril (Frontiers in Education, 2022)
School burnout is affecting more and more adolescents. In order to develop appropriate preventative measures, the problem more than ever requires a detailed understanding of the mechanisms operating on students’ capacity to adapt to circumstances rendered particularly difficult by the SARS-CoV-2 pandemic (COVID-19). In the absence of an explanatory framework in the field of school health, the JD-R model of work-related stress constitutes an original prism for reading the quality of pupils’ adaptation to their school environment. The aim of this research is on the one hand to observe the predictive links between the different variables operationalized in the school JD-R model and on the other, to test the adequacy of this model against the data in schools acutely affected by the COVID situation. A total of 470 middle school, high school and 1st year BTS students agreed to participate in the longitudinal study. They were administered six scales spread over three measurement periods. The results of the predictive path analyses reveal that the hypotheses assumed are to a good degree verified. However, even if the model as a whole does not fit the data well, in their essence, the results point to the importance of strengthening students’ own resources as well as those present within the school.